2019
DOI: 10.1109/access.2019.2950847
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Linear-to-Circular Polarization Converter Using the Graphene Transmissive Metasurface

Abstract: In this article, a tunable linear-to-circular polarization converter (LTCPC) in terahertz (THz) regime using the graphene transmissive metasurface is proposed, which is composed of two resonant layers containing the metal and graphene resonators separated by a dielectric spacer. The linearly-polarized wave with normal incidence can be transformed to the circularly-polarized wave. The operating band can be dynamically regulated in THz band by electrically controlling the Fermi energy (E f) of the graphene sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, these previously designed structures lack tunability. Therefore, peoples’ research focuses have shifted to the realization of adjustable and switchable MS [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these previously designed structures lack tunability. Therefore, peoples’ research focuses have shifted to the realization of adjustable and switchable MS [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, it has been found that metasurface can provide a convenient way to control the polarization state of EM wave. In recent years, to update the conventional design method, many different types of polarization converters have been proposed based on various anisotropic or chiral metasurfaces, which can perform different polarization conversions, such as cross polarization conversion [3][4][5][6][7][8][9][10] or linear-to-circular polarization conversion [11][12][13][14][15][16][17] . In addition, A righthanded/left-handed circularly polarized (RCP/ LCP) wave will be converted to a LCP/ RCP one after reflection on a conducting surface, however, based on a proper anisotropic or chiral metasurface, a CP-maintaining metasurface can be proposed, which can keep the handedness of the reflected wave the same as that of the CP incident one.…”
Section: Introductionmentioning
confidence: 99%
“…A tunable converter working in the terahertz frequency range and consisting of two layers of metal and graphene resonators, respectively, separated by a dielectric layer has been reported [10]. The tunability is provided by the possibility of controlling the Fermi energy of the graphene material.…”
Section: Introductionmentioning
confidence: 99%